Cognition and Behavior with Idiopathic Epilepsies - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2005)
Cognition and behavior in 42 mainstream school children with newly diagnosed idiopathic or cryptogenic epilepsy ('epilepsy only') were compared with 30 healthy gender-matched classmate controls in a 3.5-year study at Wilhelmina Children's Hospital, Utrecht, The Netherlands.